PENGARUH MODEL PEMBELAJARAN FLIPPED CLASSROOM TERHADAP HASIL BELAJAR KOGNITIF IPAS SISWA KELAS IV DI SDN 10 SINGKAWANG - Sapitri, Anis; Setyowati, Rini; Mariana, Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to: 1) To determine the significant differences in science and science cognitive learning outcomes for class IV students who are taught using the Flipped Classroom learning model and students who are taught using the direct learning model at SDN 10 Singkawang; 2) To determine the effect of the Flipped Classroom learning model on the science and science cognitive learning outcomes of class IV students at SDN 10 Singkawang. The research used was quasi-experimental research with a nonequivalent control group design. The population in this study were fourth grade students at SDN 10 Singkawang. The type of research sample used was purposive sampling. Students are given pre-test and post-test questions. To test the first hypothesis, a two-sample t-test was used and the effect size was used to test the second hypothesis. Research results: 1) There is a significant difference in the science and science cognitive learning outcomes of class IV students who were taught using the Flipped Classroom learning model and students who were taught using the direct learning model at SDN 10 Singkawang. The calculation result of is 2.43 and 2.02. Because > then Ha is accepted and Ho is rejected. 2) There is an influence of the Flipped Classroom learning model on the science and science cognitive learning outcomes of class IV students at SDN 10 Singkawang. The Effect Size calculation result is 0.67 and falls into the medium criteria.